Imaging evidence of osseous fusion of patients undergoing segmental mandibular fibular free flap reconstruction – a retrospective analysis - Dinesh Rao; Ashleigh Weyh; Mauricio Hernandez; Rachel Stein; Adam Holtzman; Sukhwinder Sandhu; Anthony Bunnell; Rui Fernandes (Journal of Clinical Imaging Science, 2026)
Objectives: There is a lack of literature detailing evidence of osseous fusion following mandibular free flap reconstruction. This purpose of this study was to determine the presence of osseous union following mandibular free flap reconstruction, the timing of fusion and risk factors associated with non-union. Material and Methods: A retrospective chart and imaging review was performed to determine the presence of fusion and risk factors for non-union following fibular free flap reconstruction of the mandible. Indications for surgery included malignancy, benign lesions, osteoradionecrosis, and trauma. Chi-square analyses were performed in aggregate and for each subgroup to determine associations between different factors for the presence of fusion. Results: This study included 79 subjects with 62 (78%) achieving at least partial fusion, and 53 (67%) achieving complete fusion. Subjects who underwent surveillance imaging for longer periods of time were more likely to achieve fusion. ( p